Geomorphic and shallow-acoustic investigation of an Antarctic Peninsula fjord system using high-resolution ROV and shipboard geophysical observations: Ice dynamics and behaviour since the Last Glacial Maximum - García, Marga; Dowdeswell, J.A.; Noormets, R.; Hogan, K.A.; Evans, J.; Ó Cofaigh, C.; Larter, R.D. (Quaternary Science Reviews, 2016)
Detailed bathymetric and sub-bottom acoustic observations in Bourgeois Fjord (Marguerite Bay, Antarctic Peninsula) provide evidence on sedimentary processes and glacier dynamics during the last glacial cycle. Submarine landforms observed in the 50 km-long fjord, from the margins of modern tidewater glaciers to the now ice-distal Marguerite Bay, are described and interpreted. The landforms are grouped into four morpho-sedimentary systems: (i) glacial advance and full-glacial; (ii) subglacial and ice-marginal meltwater; (iii) glacial retreat and neoglaciation; and (iv) Holocene mass-wasting. These morpho-sedimentary systems have been integrated with morphological studies of the Marguerite Bay continental shelf and analysed in terms of the specific sedimentary processes and/or stages of the glacial cycle. They demonstrate the action of an ice-sheet outlet glacier that produced drumlins and crag-and-tail features in the main and outer fjord. Meltwater processes eroded bedrock channels and ponds infilled by fine-grained sediments. Following the last deglaciation of the fjord at about 9000 yr BP, subsequent Holocene neoglacial activity involved minor readvances of a tidewater glacier terminus in Blind Bay. Recent stillstands and/or minor readvances are inferred from the presence of a major transverse moraine that indicates grounded ice stabilization, probably during the Little Ice Age, and a series of smaller landforms that reveal intermittent minor readvances. Mass-wasting processes also affected the walls of the fjord and produced scars and fan-shaped deposits during the Holocene. Glacier-terminus changes during the last six decades, derived from satellite images and aerial photographs, reveal variable behaviour of adjacent tidewater glaciers. The smaller glaciers show the most marked recent retreat, influenced by regional physiography and catchment-area size.
Keywords: Antarctic Peninsula; Antarktis; Fjord systems; Geomorphology; Glacial sedimentary processes; Last Glacial Maximum; ROV-Derived bathymetry; Sørishavet; batymetri; geomorfologi

Ocean mixing beneath Pine Island Glacier ice shelf, West Antarctica - Kimura, Satoshi; Jenkins, Adrian; Dutrieux, Pierre; Forryan, Alexander; Naveira Garabato, Alberto C; Firing, Yvonne (Journal of Geophysical Research: Oceans, 2016)
Ice shelves around Antarctica are vulnerable to an increase in ocean-driven melting, with the melt rate depending on ocean temperature and the strength of flow inside the ice-shelf cavities. We present measurements of velocity, temperature, salinity, turbulent kinetic energy dissipation rate, and thermal variance dissipation rate beneath Pine Island Glacier ice shelf, West Antarctica. These measurements were obtained by CTD, ADCP, and turbulence sensors mounted on an Autonomous Underwater Vehicle (AUV). The highest turbulent kinetic energy dissipation rate is found near the grounding line. The thermal variance dissipation rate increases closer to the ice-shelf base, with a maximum value found ∼0.5 m away from the ice. The measurements of turbulent kinetic energy dissipation rate near the ice are used to estimate basal melting of the ice shelf. The dissipation-rate-based melt rate estimates is sensitive to the stability correction parameter in the linear approximation of universal function of the Monin-Obukhov similarity theory for stratified boundary layers. We argue that our estimates of basal melting from dissipation rates are within a range of previous estimates of basal melting.
Keywords: Sørishavet; batymetri; brehylle; isbrem; isshelf; klimatologi; målinger; oseanografi; smeltevann; vannmasser